2016
DOI: 10.1021/acs.analchem.6b02199
|View full text |Cite
|
Sign up to set email alerts
|

Procedures for Analysis of Dried Plasma Using Microsampling Devices to Detect Sulfur Mustard-Albumin Adducts for Verification of Poisoning

Abstract: Incorporation of the chemical warfare agent sulfur mustard (SM) produces a covalent adduct with human serum albumin (HSA) representing an established plasma biomarker of poisoning. Bioanalytical verification requires both plasma generation from whole blood and shipping to specialized laboratories following strict guidelines for complex packaging. These needs often push the infrastructural boundary in crisis regions and war zones. Therefore, we herein originally introduce different reliable bioanalytical proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 23 publications
0
53
0
Order By: Relevance
“…Therefore, toxicity of SM is assumed to be due to the alkylation of proteins and DNA resulting in the functional impairment of cells, tissues, organs, and physiological processes. 12,[17][18][19][20][21][22][23] Based on the proteolysis of alkylated HSA, several analytical methods targeting the Cys 34 modification as HETE-CysProPhe (HETE-CPF) and HETE-CysPro (HETE-CP) were developed and have proven to be reliable biomarkers of exposure in vitro, in vivo, and in real cases of SM poisoning. 2 For the verification of an alleged use of SM, protein adducts reveal beneficial long-term stability of several weeks or even months in vivo when compared to products of SM hydrolysis and enzymatic biotransformation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, toxicity of SM is assumed to be due to the alkylation of proteins and DNA resulting in the functional impairment of cells, tissues, organs, and physiological processes. 12,[17][18][19][20][21][22][23] Based on the proteolysis of alkylated HSA, several analytical methods targeting the Cys 34 modification as HETE-CysProPhe (HETE-CPF) and HETE-CysPro (HETE-CP) were developed and have proven to be reliable biomarkers of exposure in vitro, in vivo, and in real cases of SM poisoning. 2 For the verification of an alleged use of SM, protein adducts reveal beneficial long-term stability of several weeks or even months in vivo when compared to products of SM hydrolysis and enzymatic biotransformation.…”
mentioning
confidence: 99%
“…Due to its bifunctional structure, crosslinks between biomolecules may occur. 12,[15][16][17][18][19][20][21][22][23][24] Herein, we present Met 329 as an additional target of SM in HSA. 15,16 Most relevant biomarkers are alkylated peptides derived from human serum albumin (HSA).…”
mentioning
confidence: 99%
“…While phosphylation is the critical step of AChE inhibition by modification of its active site serine residue, we have recently shown that the corresponding leaving group of VX (2-(diisopropylamino)ethanethiol, DPAET) is also capable of forming adducts with endogenous cysteine residues of HSA [25] . Cys-Pro dipeptides including the only free cysteine sidechain at position 34 (C 34 P) were already known to result from pronase cleavage of HSA and facilitated the identification of DPAET-CP as a novel biomarker for VX exposure in vitro [8,[14][15][16][17]25] . Enzymatic cleavage of HSA incubated with VX using pronase resulted in cysteine and proline containing small peptides.…”
Section: Resultsmentioning
confidence: 99%
“…However, today these compounds are banned by the Chemical Weapons Convention (CWC) comprising strict surveillance by the Organization for the Prohibition of Chemical Weapons (OPCW, Nobel Peace Prize 2013) [3] . For this purpose, reliable analytical methods are required allowing verification of an alleged use of CWA [5][6][7][8] . For this purpose, reliable analytical methods are required allowing verification of an alleged use of CWA [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, reactions with human serum albumin (HSA) containing the non‐disulfide bridged Cys 34 ‐residue were characterized. HSA is a suitable biomarker for SM exposure by forming HETE‐HSA but will also react with thiol compounds like NAC forming disulfide‐bridged adducts . According to Harada et al, the NAC‐HSA adduct formation happens in 2 steps .…”
Section: Introductionmentioning
confidence: 99%